KINEMATIC ANALYSIS OF TRAPEZOIDAL SUSPENSION - Adrián HAJDUČÍK; Jozef ŠKRABALA; Štefan MEDVECKÝ; František BRUMERČÍK (Scientific Journal of Silesian University of Technology. Series Transport)
This article deals with the kinematic analysis of trapezoidal suspension. Specifically, it focuses on the behaviour of the chassis when obstacle crossing was monitored. Our team is developing an autonomous mountain vehicle that will be equipped with different working adapters such as a cutter bar and a picker. The device was designed for work on slopes, hence, must be able to overcome certain natural obstacles. This implies the need to analyse the wheel suspension kinematics. The vehicle was built on a trapezoidal suspension, which has proven to be the most suitable option with respect to operating conditions. From the results obtained, it was possible to analyse the driving characteristics of the obstacle, track the rollover limits and overall safety of operation.